„Sas lelkek” és tengersík vidékek: a szabadságkép mint a Petőfi-kultusz tartós problémaforrása - Rákai, Orsolya (Studia Litteraria, 2024)
The concept of freedom plays a central role not only in Petőfi’s reception, but also in constructing the poet’s own image and it is the base of the cults of Petőfi as well. His poem, The Plains is of central importance in this process: the metaphorization and the semantization of the concept of freedom happens through this poem in public education. It is also responsible for the specifically national image of freedom which facilitates the process of making the national images of the 19-20th literature a factor in forming a collective identity. However, the central metaphor for freedom in The Plains is very specific: it expresses negation rather than standing up for values – freedom from something rather than freedom to do something. In this paper I would argue that this metaphor can be used effectively in different kinds of cults. Even though the metaphor seemingly serves its purpose well in constructing the collective identity and it can have a strong emotional-mobilizational aspect, it also poses a lot of problems for further analysis.